Perancangan User Experience Website Diskominfo Kab. Toraja Utara menggunakan Metode Human Centered Design (HCD) dengan Evaluasi User Experience Questionnaire (UEQ) - Rezdy Juliani Rapa'; Satrio Hadi Wijoyo; Andi Reza perda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Dinas Komunikasi, Informatika, Statistika dan Persandian or commonly known as Diskominfo is one of the government agencies in North Toraja district. Diskominfo in North Toraja itself founded in 2017. Now, Diskominfo in North Toraja does not yet have its own website and this is concerning, where Diskominfo which is the front guard in the field of technology and information as well as means of disseminating information within the District Government does not have an official website. Dissemination of information itself must be done through other websites, namely government website and also seek information directly by visiting the relevant agency. The purpose of this research is to design the user experience of the Diskominfo website using the Human Centered Design (HCD) approach. In designing user experience there are 6 scales that need to be considered including attractiveness, perspicuity, efficiency, dependability, stimulation and novelty. From the results of the evaluation conducted using the User Experience Questionnaire (UEQ) method, it was found that the attractiveness scale has positive mean category of 1.589 and a variance of 1.10. The perspicuity scale has a positive mean category of 1.581 and a variance vof 1.14. The efficiency scale has a positive mean category wof 1.529 and a variance of 1.07. The dependability scale has a positive mean category of 1.378 with a variance of 0.86. The stimulation scale has a positive mean category of 1.500 and a variance of 1.52. The novelty scale has a positive mean category of 0.930 and a variance of 1.79. The attractiveness, efficiency and stimulation scales are worth good while the perspicuity, dependability and novelty scales are above average.